Climate and wildfire adaptation of inland Northwest US forests. Issue 1 (13th September 2021) - Hessburg, Paul F; Charnley, Susan; Gray, Andrew N; Spies, Thomas A; Peterson, David W; Flitcroft, Rebecca L; Wendel, Kendra L; Halofsky, Jessica E; White, Eric M; Marshall, John
Abstract : After a century of intensive logging, federal forest management policies were developed in the 1990s to protect remaining large trees and old forests in the western US. Today, due to rapidly changing ecological conditions, new threats and uncertainties, and scientific advancements, some policy provisions are being re‐evaluated in interior Oregon and Washington. The case for re‐evaluation is clearest where small‐ to large‐sized, immature, fast‐growing, fire‐intolerant trees have filled in forests after both a long period of fire exclusion and the harvest of large, old trees. This infilling has created abundant fuel ladders that increase patch and landscape vulnerability to severe wildfires, which now threaten many forests. As climate change continues to alter fire regimes, we recommend that landscape‐level planning is needed to determine where fire‐tolerant and intolerant forest successional conditions are best retained on the landscape. Critical to our proposal are effective public engagement, collaboration, and tribal consultation.